Early Congenital Syphilis: The Impact of Bad Antenatal Care - Hidayatullah A, Hidayatullah; Zulmaeta, Zulmaeta (Fakultas Kedokteran Universitas Andalas, 2023)
Syphilis is a systemic infectious disease caused by Troponema palidum. Syphilis is generally transmitted through sexual contact, but can also be transmitted vertically during pregnancy. Until now syphilis has become a world wide problem for pregnant women, WHO recommends syphilis tested by triple elimination (syphilis, hepatitis B, and HIV) during antenatal care for better pregnancy outcomes.21 year old female, diagnosed with primipara 32-33 weeks of gestational age active phase of labor, latent syphilis + intrauterine single live fetus with head presentation. The patient had never checked her pregnancy until the current gestational age, and only found out that she had syphilis accompanied by clinical symptoms. Birth of a baby with suspected congenital syphilis.Â